A MODEST UV SPECTROPHOTOMETRIC ASSISTED BY CHEMOMETRIC APPROACH FOR VERIFICATION OF ACETAMINOPHEN LEVEL IN VARIOUS MANUFACTURED TABLETS AND SYRUPS IN INDONESIAN PHARMACIES - Muhammad Abdurrahman, Munir; Ahlam, Inayatullah; Sofian, Ibrahim; Imram, Radne; Rimba, Putri; Emelda, Emelda; Annisa, Fatmawati; Nurhidayanti, Nurhidayanti (Innovare Academic Sciences Pvt. Ltd., 2023)
Objective: This study aimed to verify the paracetamol level in some fabricated tablets and syrups in Indonesian pharmacies.